Effects of Group Size on Fattening Performance, Mortality Rate, Slaughter and Carcass Characteristics in Japanese Quails (Coturnix coturnix japonica) - Seker, Ibrahim; Kul, Selim; Bayraktar, Metin (Medwell Online, 2009)
This study was conducted to determine the effects of different group sizes upon fattening performance, mortality rate and slaughter and carcass characteristics in Japanese quails (Coturnix coturnix japonica). A total of 150 quails were used in the study. The quails were kept in cages with a stocking density of 125 cm(2) quail(-1) and in group sizes of 3 and 10 and were fed ad libitum. The effect of group size on live weight gain and cumulative live weight gain was found to be statistically significant in general, while its effect on live weight was insignificant. It was determined that mortality rate increased with increasing group size; however, the difference was not significant (p>0.05). The effect of group size was found to be statistically significant for feed intake between the 29-35 days (p<0.05) and between the 36-42 days (p<0.01), for cumulative feed intake only between 14-42 days (p<0.01) and for feed conversion rate between the 29-35 days, the 36-42 days and 14-42 days (p<0.05). The effect of group size was found insignificant on slaughter and carcass characteristics (except for the liver weight (p<0.05)). Consequently, it was concluded that quail breeding in cages with a stocking density of 125 cm(2) quail(-1) might yield better results with a group size of 10, when compared to a group size of 3, in terms of live weight and in particular, feed intake and feed conversion rate.
Keywords: Group size; fattening performance; mortality rate; slaughter and carcass; Japanese quail